Composite hard carbon negative electrode material, preparation method thereof and sodium ion battery
By combining phenolic resin hard carbon with microcrystalline graphite and doping tin dioxide, composite hard carbon negative electrode material is prepared, which solves the problem of insufficient circulation performance and specific capacity of the negative electrode material of sodium ion battery, and achieves higher energy density and longer service life.
Patent Information
- Application Number
- CN202510056922.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-30
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-14
AI Technical Summary
The cycling performance and specific capacity of the negative electrode material of sodium ion battery are low, resulting in insufficient service life and energy density of the battery, limiting the large-scale development and commercialization of sodium ion batteries.
By compositeing the phenolic resin hard carbon with microcrystalline graphite and doping it with a certain amount of tin dioxide, a composite hard carbon negative electrode material is prepared for sodium ion batteries. The material forms a SnO2@MG/PF hydrogel through hydrothermal reaction and high-temperature treatment, and further forms a composite hard carbon anode material through evaporation drying and high-temperature treatment.
It improves the specific capacity, Coulomb efficiency, rate performance and cycle stability of sodium ion batteries, extends the service life of the battery, and reduces the internal impedance of the battery.
Smart Images

Figure CN119873785A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a composite hard carbon negative electrode material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] In recent years, sodium-ion batteries have developed rapidly and become a high-performance energy storage system. Sodium reserves are very abundant in nature. Its concentration in seawater is nearly five orders of magnitude higher than that of lithium. It accounts for 2.74% of the total mass of the earth's crust and is widely distributed. The abundance of this resource effectively reduces the cost of raw materials, making sodium-ion batteries (SIBs) gradually surpass lithium-ion batteries (LIBs) and become a more ideal energy storage option.
[0003] Similar to lithium, sodium also belongs to the first group of elements and has similar chemical properties. Sodium-ion batteries use a similar deintercalation mechanism as lithium-ion batteries, that is, during the charge and discharge process, Na + Ions migrate back and forth between the positive and negative electrodes to achieve energy storage and release. However, compared with lithium, the relative atomic mass of sodium is higher, resulting in a relatively low theoretical specific capacity. + The radius of the ion is Li + Larger (Na + Radius: 0.106 nm, Li + radius: 0.076nm), making Na + The embedding / de-embedding in the electrode material becomes more difficult, resulting in problems such as decreased battery cycle performance and reduced specific capacity, which seriously restricts the large-scale development and commercialization of sodium-ion batteries.
[0004] Current research is focused on finding alternatives to negative electrode materials for sodium-ion batteries, which need to have high specific capacity and substitutability. Research objects include porous hard carbon, transition metal oxides, transition metal phosphides and metal alloys. Traditional porous hard carbon has high capacity and high rate performance, but due to poor sodium storage structure, it is difficult to desolvate, resulting in low sodium storage capacity, obvious electrolyte side reactions, and low first coulombic efficiency and cycle coulombic efficiency. During the charge and discharge process under high rate and long cycle conditions, rapid sodium ion insertion / extraction will lead to degradation of the micro- and nanostructure of the negative electrode material, volume expansion may cause the negative electrode material to separate from the current collector, and kinetic limitations related to the discontinuous electron transfer structure of the electrode will also affect stability. Summary of the invention
[0005] In view of the problems existing in the use of existing graphite as negative electrode materials for sodium ion batteries, the present invention uses a composite hard carbon negative electrode material obtained by compounding phenolic resin hard carbon and microcrystalline graphite and then doping it with a certain amount of tin dioxide in sodium ion batteries, which can improve the specific capacity, coulombic efficiency, rate and cycle performance of the sodium ion battery.
[0006] The first object of the present invention is to provide a method for preparing a composite hard carbon negative electrode material, comprising the following steps:
[0007] S1: Add SnCl4·5H2O to the suspension of microcrystalline graphite / phenolic resin hard carbon and stir evenly for 1 h to obtain a mixed solution A;
[0008] S2: placing the mixed solution A in an autoclave for hydrothermal reaction, and then soaking and washing in deionized water to obtain SnO2@MG / PF hydrogel after the reaction is completed;
[0009] S3 evaporates and dries the SnO2@MG / PF hydrogel under the protection of inert gas, and then places it in a high-temperature furnace for high-temperature treatment to obtain a composite hard carbon negative electrode material.
[0010] Specifically, the preparation method of the phenolic resin hard carbon in step S1 is: 0.2 g of resorcinol, 0.3 ml of ammonia water, 8 ml of anhydrous ethanol and 48 ml of deionized water are mixed uniformly to obtain a mixed solution a; then 0.28 ml of formaldehyde solution is added to the mixed solution a, and stirred uniformly at 60°C for 24 hours to obtain a phenolic resin-based precursor; the phenolic resin-based precursor is carbonized at a high temperature of 1600°C for 6 hours to obtain a phenolic resin hard carbon.
[0011] Specifically, the preparation method of the microcrystalline graphite / phenolic resin hard carbon suspension in step S1 is: placing microcrystalline graphite and phenolic resin hard carbon in deionized water in turn, stirring evenly at 25-45° C. for 6-8 hours to obtain a microcrystalline graphite / phenolic resin hard carbon suspension.
[0012] Specifically, the concentration of the suspension of microcrystalline graphite / phenolic resin hard carbon in step S1 is 6 mg / mL; the size of the microcrystalline graphite is 200 mesh.
[0013] Specifically, in step S1, the mass ratio of SnCl4·5H2O, microcrystalline graphite and phenolic resin hard carbon is 3:2:3.
[0014] Specifically, the reaction temperature of the hydrothermal reaction in step S2 is 180-200° C., and the reaction time is 6-10 hours.
[0015] Specifically, the evaporation drying treatment in step S3 is performed at a temperature of 80 to 120° C. and for a time of 0.5 to 2 hours.
[0016] Specifically, the high temperature treatment in step S3 has a treatment temperature of 1000-1200° C., a heating rate of 1-5° C. / min, and a treatment time of 6 hours.
[0017] Specifically, the inert gas in step S3 is any one of nitrogen, argon and helium.
[0018] The second object of the present invention is to provide a composite hard carbon negative electrode material prepared by the above preparation method.
[0019] The second object of the present invention is to provide a sodium ion battery, which is composed of a positive electrode, a negative electrode, an electrolyte and a separator, and the negative electrode material used in the negative electrode is the composite hard carbon negative electrode material described above.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] Since microcrystalline graphite itself has high conductivity, its arranged graphite lattice structure is conducive to the rapid conduction of electrons in the plane; and the hard carbon formed by pyrolysis of phenolic resin can form more conductive channels in the structure through compounding with microcrystalline graphite, reduce the area of uneven conductivity in the carbon material, and thus improve the conductivity of the entire material. After SnO2 is compounded with microcrystalline graphite / phenolic resin hard carbon material as a semiconductor material, it can form a close interface contact with the carbon material, forming a carbon-non-carbon hybrid nano-scale dispersed phase and porous network structure on the surface of the material, providing a large specific surface area for the composite hard carbon negative electrode material, and promoting the transmission of sodium ions during the charge and discharge process. In addition, SnO2 is also doped in the porous structure of the composite hard carbon negative electrode material, which improves the specific capacity and conductivity of the negative electrode material. The unique structure can also effectively inhibit the volume expansion change of the negative electrode sheet during the charge and discharge process, prevent agglomeration, reduce the polarization of the electrode material and the internal resistance of the battery, and improve the cycle stability and rate performance of the material. Through the synergistic effect between microcrystalline graphite, phenolic resin hard carbon and SnO2, the advantages of the three are fully utilized and complement each other in structure and properties. The composite hard carbon negative electrode material has the advantages of both traditional hard carbon materials and nano-doped materials, with increased specific surface area, improved conductivity, excellent electrochemical properties, and enhanced thermal conductivity and structural stability, indicating that it has great potential in high-capacity, high-power and high-safety application fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A schematic diagram of the structure of the composite hard carbon negative electrode material a1 provided in Example 1 of the present invention;
[0023] Figure 2 This is a SEM image of the composite hard carbon negative electrode material a1 provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0024] The following will combine the contents in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Unless otherwise defined, all technical and scientific terms used in this specification have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used in this specification includes any and all combinations of one or more of the related listed items.
[0026] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are all commercially available unless otherwise specified.
[0027] Example 1
[0028] The preparation method of the composite hard carbon negative electrode material a1 involved in this embodiment 1 includes the following steps:
[0029] (1) Preparation of phenolic resin hard carbon:
[0030] 0.2 g of resorcinol, 0.3 ml of ammonia water, 8 ml of anhydrous ethanol and 48 ml of deionized water were mixed uniformly to obtain a mixed solution a1; 0.28 ml of formaldehyde solution was added to the mixed solution a1, and the mixture was stirred uniformly at 60°C for 24 hours to obtain a phenolic resin-based precursor a1; the phenolic resin-based precursor a1 was carbonized at a high temperature of 1600°C for 6 hours to obtain the phenolic resin hard carbon prepared in Example 1.
[0031] (2) Preparation of composite hard carbon negative electrode materials:
[0032] Step 1: Place 0.6 g of microcrystalline graphite and 0.9 g of phenolic resin hard carbon in 250 ml of deionized water, and stir evenly for 6 h at 25 ° C to obtain a suspension of microcrystalline graphite / phenolic resin hard carbon with a concentration of 6 mg / mL. Add 0.9 g of tin chloride pentahydrate (SnCl4·5H2O) as a precursor of SnO2 to the microcrystalline graphite / phenolic resin hard carbon suspension, stir evenly for 1 h, and obtain the mixed solution A1 prepared in Example 1.
[0033] Step 2: Place the mixed solution A1 in an autoclave and perform hydrothermal reaction at 180°C for 6 hours. After the reaction, soak and wash the product in deionized water to remove excess Sn. 4+, and the cylindrical SnO2@MG / PF hydrogel prepared in Example 1 was obtained.
[0034] Step 3: Place the cylindrical SnO2@MG / PF hydrogel prepared in Example 1 in a vacuum drying oven, and evaporate and dry it at 100°C for 1.5 hours under nitrogen protection. Then place the evaporated and dried SnO2@MG / PF hydrogel in a high-temperature furnace, heat it to 1200°C at a rate of 5°C / min, and treat it at high temperature for 6 hours to obtain the composite hard carbon negative electrode material a1 prepared in Example 1.
[0035] (3) Preparation of negative electrode sheet: The composite hard carbon negative electrode material a1, binder (CMC BH90), and conductive agent SP were mixed in a mass ratio of 8:1:1 and coated on the current collector aluminum foil. After vacuum drying at 105°C for 10 h, the mixture was pressed at a pressure of 1 MPa and punched into a negative electrode sheet.
[0036] See also Figure 1 , Figure 1 The structural diagram of the composite hard carbon negative electrode material a1 provided in Example 1 is as follows: Figure 1 It can be seen that in the present invention, through the compounding of microcrystalline graphite and phenolic resin hard carbon, more conductive channels can be formed in the structure, reducing the area of uneven conductivity in the carbon material. After SnO2 is compounded with microcrystalline graphite / phenolic resin hard carbon material as a semiconductor material, it can form a close interface contact with the carbon material, forming a carbon-non-carbon hybrid nano-scale dispersed phase and porous network structure on the surface of the material, and SnO2 is also doped in the porous structure. The unique structure formed by the present invention can also effectively inhibit the volume expansion change of the negative electrode during the charge and discharge process, prevent agglomeration, reduce the polarization of the electrode material and the internal resistance of the battery, and improve the cycle stability and rate performance of the material. Figure 2 This is a SEM image of the composite hard carbon negative electrode material a1 provided in Example 1 of the present invention. Figure 2 It can be seen that the composite hard carbon negative electrode material a1 prepared according to the above method is granular, the particles are evenly distributed as a whole, there is no adhesion between the particles, and due to the small pore size belonging to the micropore level, no macropores and defective structures were found.
[0037] Example 2
[0038] The preparation method of the composite hard carbon negative electrode material a2 involved in this embodiment 2 includes the following steps:
[0039] (1) Preparation of phenolic resin hard carbon:
[0040] 0.2 g of resorcinol, 0.3 ml of ammonia water, 8 ml of anhydrous ethanol and 48 ml of deionized water were mixed uniformly to obtain a mixed solution a1; 0.28 ml of formaldehyde solution was added to the mixed solution a1, and the mixture was stirred uniformly at 60°C for 24 hours to obtain a phenolic resin-based precursor a1; the phenolic resin-based precursor a1 was carbonized at a high temperature of 1600°C for 6 hours to obtain the phenolic resin hard carbon prepared in Example 2.
[0041] (2) Preparation of composite hard carbon negative electrode materials:
[0042] Step 1: Place 1 g of microcrystalline graphite and 1.5 g of phenolic resin hard carbon in 417 ml of deionized water, and stir evenly at 45°C for 8 h to obtain a suspension of microcrystalline graphite / phenolic resin hard carbon with a concentration of 6 mg / mL. Add 1.5 g of SnCl4·5H2O to the microcrystalline graphite / phenolic resin hard carbon suspension, and stir evenly for 1 h to obtain the mixed solution A2 prepared in Example 2.
[0043] Step 2: Place the mixed solution A2 in an autoclave and perform hydrothermal reaction at 200°C for 10 h. After the reaction, soak the product in deionized water for 48 h to wash and remove excess Sn. 4+ , and the cylindrical SnO2@MG / PF hydrogel prepared in Example 2 was obtained.
[0044] Step 3: Place the cylindrical SnO2@MG / PF hydrogel prepared in Example 2 in a vacuum drying oven, and evaporate and dry it at 120°C for 2 hours under argon protection. Then place the evaporated and dried SnO2@MG / PF hydrogel in a high-temperature furnace, heat it to 1100°C at a rate of 3°C / min, and treat it at high temperature for 6 hours to obtain the composite hard carbon negative electrode material a2 prepared in Example 2.
[0045] (3) Preparation of negative electrode sheet: The composite hard carbon negative electrode material a2, binder (CMC BH90), and conductive agent SP were mixed in a mass ratio of 8:1:1 and coated on the current collector aluminum foil. After vacuum drying at 105°C for 10 h, the mixture was pressed at a pressure of 1 MPa and punched into a negative electrode sheet.
[0046] Example 3
[0047] The preparation method of the composite hard carbon negative electrode material a3 involved in this embodiment 3 includes the following steps:
[0048] (1) Preparation of phenolic resin hard carbon:
[0049] 0.2 g of resorcinol, 0.3 ml of ammonia water, 8 ml of anhydrous ethanol and 48 ml of deionized water were mixed uniformly to obtain a mixed solution a1; 0.28 ml of formaldehyde solution was added to the mixed solution a1, and the mixture was stirred uniformly at 60°C for 24 hours to obtain a phenolic resin-based precursor a1; the phenolic resin-based precursor a1 was carbonized at a high temperature of 1600°C for 6 hours to obtain the phenolic resin hard carbon prepared in Example 3.
[0050] (2) Preparation of composite hard carbon negative electrode materials:
[0051] Step 1: 0.8 g of microcrystalline graphite and 1.2 g of phenolic resin hard carbon were placed in 334 ml of deionized water, and stirred evenly at 30°C for 7 h to obtain a suspension of microcrystalline graphite / phenolic resin hard carbon with a concentration of 6 mg / mL. 1.2 g of SnCl4·5H2O was added to the microcrystalline graphite / phenolic resin hard carbon suspension, and stirred evenly for 1 h to obtain the mixed solution A3 prepared in Example 3.
[0052] Step 2: Place the mixed solution A3 in an autoclave and perform a hydrothermal reaction at 185°C for 8 hours. After the reaction, soak the product in deionized water for 48 hours to wash and remove excess Sn. 4+ , and the cylindrical SnO2@MG / PF hydrogel prepared in Example 3 was obtained.
[0053] Step 3: Place the cylindrical SnO2@MG / PF hydrogel prepared in Example 3 in a vacuum drying oven, and evaporate and dry it at 90°C for 1 hour under argon protection. Then place the evaporated and dried SnO2@MG / PF hydrogel in a high-temperature furnace, heat it to 1050°C at a rate of 2°C / min, and treat it at high temperature for 6 hours to obtain the composite hard carbon negative electrode material a3 prepared in Example 3.
[0054] (3) Preparation of negative electrode sheet: The composite hard carbon negative electrode material a3, binder (CMC BH90), and conductive agent SP were mixed in a mass ratio of 8:1:1 and coated on the current collector aluminum foil. After vacuum drying at 105°C for 10 h, the mixture was pressed at a pressure of 1 MPa and punched into a negative electrode sheet.
[0055] Example 4
[0056] The preparation method of the composite hard carbon negative electrode material a4 involved in this embodiment 4 includes the following steps:
[0057] (1) Preparation of phenolic resin hard carbon:
[0058] 0.2 g of resorcinol, 0.3 ml of ammonia water, 8 ml of anhydrous ethanol and 48 ml of deionized water were mixed uniformly to obtain a mixed solution a1; 0.28 ml of formaldehyde solution was added to the mixed solution a1, and the mixture was stirred uniformly at 60°C for 24 hours to obtain a phenolic resin-based precursor a1; the phenolic resin-based precursor a1 was carbonized at a high temperature of 1600°C for 6 hours to obtain the phenolic resin hard carbon prepared in Example 4.
[0059] (2) Preparation of composite hard carbon negative electrode materials:
[0060] Step 1: 0.6 g of microcrystalline graphite and 0.9 g of phenolic resin hard carbon were placed in 250 ml of deionized water, and stirred evenly at 30°C for 7 h to obtain a suspension of microcrystalline graphite / phenolic resin hard carbon with a concentration of 6 mg / mL. 0.9 g of SnCl4·5H2O was added to the microcrystalline graphite / phenolic resin hard carbon suspension, and stirred evenly for 1 h to obtain the mixed solution A4 prepared in Example 4.
[0061] Step 2: Place the mixed solution A4 in an autoclave and perform hydrothermal reaction at 185°C for 7 hours. After the reaction, soak the product in deionized water for 48 hours to wash and remove excess Sn. 4+ , and the cylindrical SnO2@MG / PF hydrogel prepared in Example 4 was obtained.
[0062] Step 3: Place the cylindrical SnO2@MG / PF hydrogel prepared in Example 4 in a vacuum drying oven, and evaporate and dry it at 110°C for 0.5h under helium protection. Then place the evaporated and dried SnO2@MG / PF hydrogel in a high-temperature furnace, heat it to 1200°C at a rate of 5°C / min, and treat it at high temperature for 6h to obtain the composite hard carbon negative electrode material a4 prepared in Example 4.
[0063] (3) Preparation of negative electrode sheet: The composite hard carbon negative electrode material a4, binder (CMC BH90), and conductive agent SP were mixed in a mass ratio of 8:1:1 and coated on the current collector aluminum foil. After vacuum drying at 105°C for 10 h, the mixture was pressed at a pressure of 1 MPa and punched into a negative electrode sheet.
[0064] Comparative Example 1
[0065] The difference between Comparative Example 1 and Example 1 is that no microcrystalline graphite is added to the composite hard carbon negative electrode material obtained therein.
[0066] The preparation method of the composite hard carbon negative electrode material b1 involved in this comparative example 1 comprises the following steps:
[0067] (1) Preparation of phenolic resin hard carbon:
[0068] 0.2 g of resorcinol, 0.3 ml of ammonia water, 8 ml of anhydrous ethanol and 48 ml of deionized water were mixed uniformly to obtain a mixed solution a1; 0.28 ml of formaldehyde solution was added to the mixed solution a1, and the mixture was stirred uniformly at 60°C for 24 hours to obtain a phenolic resin-based precursor a1; the phenolic resin-based precursor a1 was carbonized at a high temperature of 1600°C for 6 hours to obtain the phenolic resin hard carbon prepared in Example 1.
[0069] (2) Preparation of composite hard carbon negative electrode materials:
[0070] Step 1: Place 0.9 g of phenolic resin hard carbon in 150 ml of deionized water and stir evenly for 6 h at 25 ° C to obtain a suspension of phenolic resin hard carbon with a concentration of 6 mg / mL. Add 0.9 g of SnCl4·5H2O as a precursor of SnO2 to the phenolic resin hard carbon suspension and stir evenly for 1 h to obtain the mixed solution B1 prepared in Comparative Example 1.
[0071] Step 2: Place the mixed solution B1 in an autoclave and perform hydrothermal reaction at 180°C for 6 hours. After the reaction, soak and wash the product in deionized water to remove excess Sn. 4+ , and the SnO2@PF hydrogel prepared in Comparative Example 1 was obtained.
[0072] Step 3: Place the SnO2@PF hydrogel prepared in Example 1 in a vacuum drying oven, and evaporate and dry it at 100°C for 1.5 hours under nitrogen protection. Then place the evaporated and dried SnO2@PF hydrogel in a high-temperature furnace, heat it to 1200°C at a rate of 5°C / min, and treat it at high temperature for 6 hours to obtain the composite hard carbon negative electrode material b1 prepared in Comparative Example 1.
[0073] (3) Preparation of negative electrode sheet: The composite negative electrode material b1, binder (CMC BH90), and conductive agent SP were mixed in a mass ratio of 8:1:1 and coated on the current collector aluminum foil. After vacuum drying at 105°C for 10 h, the mixture was pressed at a pressure of 1 MPa and punched into a negative electrode sheet.
[0074] Comparative Example 2
[0075] The difference between Comparative Example 1 and Example 1 is that no phenolic resin hard carbon is added to the obtained composite negative electrode material.
[0076] The preparation method of the composite negative electrode material b2 involved in this comparative example 2 comprises the following steps:
[0077] Step 1: Place 0.6 g of microcrystalline graphite in 100 ml of deionized water and stir evenly for 6 h at 25 ° C to obtain a suspension of microcrystalline graphite with a concentration of 6 mg / mL. Add 0.6 g of tin chloride pentahydrate (SnCl4·5H2O) as a precursor of SnO2 to the suspension of microcrystalline graphite and stir evenly for 1 h to obtain a mixed solution B2 prepared in Comparative Example 2.
[0078] Step 2: Place the mixed solution B2 in an autoclave and perform hydrothermal reaction at 180°C for 6 hours. After the reaction, soak and wash the product in deionized water to remove excess Sn. 4+ , and the SnO2@MG hydrogel prepared in Comparative Example 2 was obtained.
[0079] Step 3: Place the SnO2@MG hydrogel prepared in Comparative Example 2 in a vacuum drying oven, and evaporate and dry it at 100°C for 1.5 hours under nitrogen protection. Then place the evaporated and dried SnO2@MG hydrogel in a high-temperature furnace, heat it to 1200°C at a rate of 5°C / min, and treat it at high temperature for 6 hours to obtain the composite negative electrode material b2 prepared in Comparative Example 2.
[0080] (3) Preparation of negative electrode sheet: The composite negative electrode material b2, binder (CMC BH90), and conductive agent SP were mixed in a mass ratio of 8:1:1 and coated on the current collector aluminum foil. After vacuum drying at 105°C for 10 h, the mixture was pressed at a pressure of 1 MPa and punched into a negative electrode sheet.
[0081] Performance Testing
[0082] The negative electrode sheets prepared in Examples 1-4 and Comparative Examples 1-2 were used as negative electrodes, metallic sodium was used as positive electrodes, and the electrolyte was 1 mol / L NaPF6 or NaClO4. After injection, packaging and other processes, a sodium ion battery was prepared. The first reverse specific capacity test at 0.1C rate and the first coulomb efficiency test were carried out at 25°C. After 50 cycles at 0.1C rate, the charge specific capacity of 50 cycles was measured. The specific results are shown in Table 1 below.
[0083] Table 1
[0084]
[0085] It can be seen from Table 1 that the sodium ion batteries prepared in Examples 1-4 can still maintain a specific capacity of about 200 mAh / g after 50 cycles, and the capacity attenuation rate is less than 12%. In addition, the first coulombic efficiency and rate performance are significantly improved compared with those of Comparative Examples 1-2. It can be seen that the sodium ion batteries prepared in Examples 1-4 all exhibit high specific capacity, high first efficiency, high rate and long cycle stability.
[0086] It can be seen that through the synergistic effect between microcrystalline graphite, phenolic resin hard carbon and SnO2, the advantages of the three are fully utilized to construct a composite hard carbon material with a unique carbon-non-carbon hybrid structure. After SnO2 is composited with microcrystalline graphite / phenolic resin hard carbon materials as a semiconductor material, it can form a close interface contact with the carbon material, forming a carbon-non-carbon hybrid nano-scale dispersed phase and porous network structure on the surface of the material, providing a large specific surface area for the composite hard carbon negative electrode material, and promoting the transmission of sodium ions during the charge and discharge process. In addition, SnO2 is also doped in the pores of the composite hard carbon negative electrode material, which further improves the specific capacity and conductivity of the negative electrode material. The prepared composite hard carbon negative electrode material has the advantages of traditional hard carbon materials, and at the same time, the thermal conductivity, specific capacity, cycle stability and rate performance are also significantly improved.
[0087] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.
[0088] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0089] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a composite hard carbon negative electrode material, characterized in that: The following steps are involved: S1: Add SnCl4·5H2O to the suspension of microcrystalline graphite / phenolic resin hard carbon and stir evenly for 1 h to obtain a mixed solution A; S2: placing the mixed solution A in an autoclave for hydrothermal reaction, and then soaking and washing in deionized water to obtain SnO2@MG / PF hydrogel after the reaction is completed; S3 evaporates and dries the SnO2@MG / PF hydrogel under the protection of inert gas, and then places it in a high-temperature furnace for high-temperature treatment to obtain a composite hard carbon negative electrode material.
2. The preparation method according to claim 1, characterized in that: The preparation method of the phenolic resin hard carbon described in step S1 is: 0.2g of resorcinol, 0.3ml of ammonia water, 8ml of anhydrous ethanol and 48ml of deionized water are mixed uniformly to obtain a mixed solution a; then 0.28ml of formaldehyde solution is added to the mixed solution a, and stirred uniformly at 60°C for 24h to obtain a phenolic resin-based precursor; the phenolic resin-based precursor is carbonized at a high temperature of 1600°C for 6h to obtain a phenolic resin hard carbon.
3. The preparation method according to claim 1, characterized in that: The preparation method of the microcrystalline graphite / phenolic resin hard carbon suspension in step S1 is: placing microcrystalline graphite and phenolic resin hard carbon in deionized water in turn, stirring evenly at 25-45° C. for 6-8 hours to obtain a microcrystalline graphite / phenolic resin hard carbon suspension.
4. The preparation method according to claim 1, characterized in that: The concentration of the suspension of microcrystalline graphite / phenolic resin hard carbon in step S1 is 6 mg / mL; the size of the microcrystalline graphite is 200 mesh.
5. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of SnCl4·5H2O, microcrystalline graphite and phenolic resin hard carbon is 3:2:
3.
6. The preparation method according to claim 1, characterized in that: The reaction temperature of the hydrothermal reaction in step S2 is 180-200° C., and the reaction time is 6-10 hours.
7. The preparation method according to claim 1, characterized in that: The treatment temperature of the evaporation drying treatment in step S3 is 80-120° C., and the treatment time is 0.5-2 h; the treatment temperature of the high temperature treatment is 1000-1200° C., the heating rate is 1-5° C. / min, and the treatment time is 6 h.
8. The preparation method according to claim 1, characterized in that: The inert gas in step S3 is any one of nitrogen, argon and helium.
9. A composite hard carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 8.
10. A sodium ion battery, comprising a positive electrode, a negative electrode, an electrolyte and a diaphragm, characterized in that: The negative electrode material used in the negative electrode is the composite hard carbon negative electrode material as claimed in claim 9.
Citation Information
Patent Citations
Organic cathode material for sodium ion battery
CN103456961A
Hard carbon material and preparation method thereof
CN115332532A
Tin-hard carbon negative electrode material, preparation method thereof and sodium ion battery
CN116979028A
Phenolic resin-based carbon tin composite material, preparation method, negative electrode active material and sodium secondary battery
CN117712351A
Composite material and method for preparing the same, electrochemical device, and electronic device
JP2023154027A
Cited By
Pulse mercury-free zinc air button cell and preparation method thereof
CN120999199A